2006
DOI: 10.1210/me.2005-0357
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 9 Is Antiapoptotic during Follicular Development from Preantral to Early Antral Stage

Abstract: Ovarian follicular atresia represents a selection process that ensures the release of only healthy and viable oocytes during ovulation. The transition from preantral to early antral stage is the penultimate stage of development in terms of gonadotropin dependence and follicle destiny (survival/growth vs. atresia). We have examined whether and how oocyte-derived growth differentiation factor 9 (GDF-9) and FSH regulate follicular development and atresia during the preantral to early antral transition, by a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
95
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(106 citation statements)
references
References 67 publications
9
95
0
2
Order By: Relevance
“…In the present study, we observed a significant effect of GDF-9, IGF-I and GH alone or combined, enhancing the survival of goat preantral follicles, except when GDF-9/IGF-I and GDF-9/GH were used, since there was no synergistic effect between these compounds when combined. Orisaka et al (28) suggested that GDF-9 promotes follicular survival and growth during the preantral to early antral transition by suppressing granulosa cell apoptosis and follicular atresia. Deletion of the GDF-9 gene in mice blocked folliculogenesis at the primary stage, demonstrating the importance of this growth factor in early follicular development (29).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed a significant effect of GDF-9, IGF-I and GH alone or combined, enhancing the survival of goat preantral follicles, except when GDF-9/IGF-I and GDF-9/GH were used, since there was no synergistic effect between these compounds when combined. Orisaka et al (28) suggested that GDF-9 promotes follicular survival and growth during the preantral to early antral transition by suppressing granulosa cell apoptosis and follicular atresia. Deletion of the GDF-9 gene in mice blocked folliculogenesis at the primary stage, demonstrating the importance of this growth factor in early follicular development (29).…”
Section: Discussionmentioning
confidence: 99%
“…GDF9 and BMP15 are oocyte paracrine factors whose functions in follicular development have been well elaborated (Dong et al 1996, Vitt et al 2000, Otsuka et al 2001, Yan et al 2001, Otsuka & Shimasaki 2002, Shimasaki et al 2004, Gilchrist et al 2006, Yoshino et al 2006, Sugiura et al 2007, Edwards et al 2008, Su et al 2008. GDF9 is expressed in oocytes in mice and humans (McGrath et al 1995, Aaltonen et al 1999 and plays a key role in normal follicular development (Elvin et al 1999, Orisaka et al 2006. Interestingly, our data indicated that knockdown of ALK2/3/6 ALK4/5/7 SMAD7 SMAD7 ?…”
Section: Discussionmentioning
confidence: 65%
“…This balance disturbance is in turn one of the reasons of ovarian cyst formation [25]. Namely, the transition of the follicle from the preantral to early antral stage is the "penultimate" stage of development in terms of gonadotropin dependence and follicle destiny [growth versus atresia] [26]. Follicles selected for further development are thought to receive precise gonadotropic and intra-ovarian regulatory signals for survival, whereas follicular atresia is a consequence of inadequate growth support [27].…”
Section: Discussionmentioning
confidence: 99%